2010
DOI: 10.1007/s10120-009-0530-y
|View full text |Cite
|
Sign up to set email alerts
|

Multidetector computed tomography for preoperative identification of left gastric vein location in patients with gastric cancer

Abstract: Background. The area near the left gastric vein (LGV) is a challenging site at which to perform dissection of the lymph nodes during gastrectomy. Therefore, knowledge of the precise location of the LGV is important. The objective of this study was to examine the usefulness of multidetector computed tomography (MDCT) for the identifi cation of the LGV. Methods. Eighty-one patients with gastric cancer underwent MDCT, which was performed with contrast media in 76 patients and without contrast media in 5 patients.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 10 publications
1
20
0
Order By: Relevance
“…Preoperative familiarity with the anatomical features of the LGV is therefore required to avoid accidental dissection of the LGV. Analysis of abdominal CT results of 81 patients showed that the LGV locations could be detected by MDCT preoperatively in 76 patients (93.8 %) [11]. Similarly, we found that LGV locations could be detected by CT reconstruction.…”
Section: Discussionsupporting
confidence: 68%
“…Preoperative familiarity with the anatomical features of the LGV is therefore required to avoid accidental dissection of the LGV. Analysis of abdominal CT results of 81 patients showed that the LGV locations could be detected by MDCT preoperatively in 76 patients (93.8 %) [11]. Similarly, we found that LGV locations could be detected by CT reconstruction.…”
Section: Discussionsupporting
confidence: 68%
“…Computed tomography (CT) analysis of the LGV's path has already been performed as part of the laparoscopic treatment of gastric cancer, 2 to locate the vein before surgery and reduce the bleeding that could result from dissection along the common hepatic artery (CHA) during a gastrectomy for cancer 3,4 . However, we are not aware of similar studies concerning the pre‐operative analysis of the LGV before a pancreatectomy.…”
Section: Introductionmentioning
confidence: 99%
“…The recent development of multidetector computed tomography (MDCT) makes it possible to perform threedimensional CT angiography (3D CTA) imaging, which appears to be an effective and reliable technique for recognizing the perigastric vascular anatomy [6][7][8][9][10][11][12][13]. However, this technique requires at least two scanning phases.…”
Section: Introductionmentioning
confidence: 99%